ADDITION OF VARIOUS CONCENTRATIONS OF SUGARCANE WATER TO EGG YOLK PHOSPHATE DILUENT ON THE QUALITY OF CEMANI CHICKEN SPERMATOZOA STORED FOR 48 HOURS - Ni Wayan Ayu Sri Sedani; Wayan Bebas; I Wayan Sukernayasa (Buletin Veteriner Udayana, 2025)
Semen diluent is a solution that serves to maintain the quality of spermatozoa during storage and facilitate artificial insemination. The use of natural-based diluents is still rare, so it is necessary to develop diluents that utilize available natural resources. This study aimed to evaluate the effect of adding various concentrations of sugarcane water in egg yolk phosphate diluent on the quality of Cemani chicken semen stored for 48 hours at 5°C. This study used three cemani chickens with an age range of approximately seven months, in a healthy condition, and trained to collect sperm. The process of collecting chicken semen is done by massage method. This study used a completely randomized design with six treatments, namely the addition of sugarcane water as much as 0%, 5%, 10%, 15%, 20%, and 25%. Semen was stored for 48 hours at 5˚C. Parameters observed were motility, viability, and abnormality of spermatozoa. Each treatment was repeated four times. Data were analyzed using ANOVA test, followed by Ducan test if there were significant differences. The results showed that 20% egg yolk phosphate diluent with various concentrations of water had a significant effect (P<0.05) on motility, viability, and abnormality of cemani chicken semen. After the Ducan test, treatment T3 (phosphate buffer + 20% egg yolk + 15% cane water) produced the best semen quality, when compared to T0, T1, T2, T4, and T5, with a motility percentage of 62.50 ± 2.08%, viability 70.75 ± 2.75%, and abnormality 8.25 ± 0.96%. So, it can be concluded that the diluent formula that has the best results on the quality of spermatozoa stored for 48 hours is the treatment in phosphate buffer 20% egg yolk + 15% sugarcane water.